AN ANALYSIS OF THE IMPACT OF PEER EDITING ON STUDENTS’ WRITING OF CLASS XI, LANGUAGE DIVISION OF SMA NEGERI 2 KUPANG - Rocky Paulus Sekoni; Sanhedri Boimau (Universitas Muhammadiyah Makassar, 2021)
This study was undertaken to determine the influence of peer editing on SMA Negeri 2 Kupang students' writing in argumentative and descriptive, as well as the components of writing that were altered, the impact on the students' writing scores and also the comparison impact of this peer editing based on students’ gender. To support the findings, this study is classified as dominating descriptive qualitative and blended with descriptive quantitative methods. However, the use of qualitative here is just to support the finding by expressing the influence of peer editing on students' writing through scoring. The findings of this study reveal that peer editing has both beneficial and negative effects on students' argumentative writing. The dominant impact found in this students’ writing is positive impact because there is only one negative impact has been determined. As the conclusion, this peer editing has some positive impacts to the component of writing such as, component of grammar, content, vocabulary, organization and mechanic. Second, the most positive impact of applying peer editing in argumentative writing is on the component of grammar. Third, the most component of writing that have been edited by the peers is grammar. Fourth, from the score of writing have been calculated, it is known that students’ writing score after editing session is more increase. Fifth, the result shows that most of editing have done in the argumentative writing is focus on grammatical component, and vocabulary, because from 59 from 74 editing is applied on grammatical component. The last, the comparison impact between male and female students writing is dominantly conducted on female students writing result and score.